Analisis Program Pendidikan Karakter (PPK) di SD N Muntung Selama Masa Pandemi Covid-19 - Sasa Rofi Ramadani; Prasena Arisyanto; Diana Endah Handayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of the study was to determine school policies related to learning during the covid 19 pandemic. To find out the implementation of strengthening character education at SD N Muntung during the covid 19 pandemic. Qualitative research methods. Using interactive analysis techniques with stages of data collection, data reduction, data presentation and drawing conclusions. The results of the study are school policies related to learning during the COVID-19 pandemic including initiating new policies regarding learning during the pandemic as well as the efforts and constraints of schools conducting learning during the pandemic as well as implementing strengthening character education at SD N Muntung during the COVID-19 pandemic including socialization to stakeholders, development in activities schools, involvement of school residents in character building during the covid 19 pandemic, activities and facilities that support character formation during the covid 19 pandemic as well as obstacles and influences in implementing character education strengthening during the pandemic.